(4a-12)+3a= 6a+1
Combine like terms.
7a-12= 6a+1
Add 12 to the other side.
7a= 6a+13
Subtract 6a on both sides.
a= 13
I hope this helps!
~kaikers
Answer:
C
Step-by-step explanation:
Here’s the surface area formulas for different shapes
Answer:
Step-by-step explanation:
<u>Given</u>
Need to complete square on the left side of equation
<u>The square should be in the form of:</u>
<u>We see a = x therefore </u>
- 2b = -3/4, so
- b = -3/8 and
- b² = (-3/8)² = 9/64
So the missing constant term is 9/64
Answer:
Step-by-step explanation:
What the hell is that